Simpanan Karbon pada Padang Lamun di Perairan Tanjung Benoa, Bali - Parnata, I Komang Agus; Putra, I Dewa Nyoman Nurweda; Indrawan, Gede Surya (Journal of Marine and Aquatic Sciences, 2020)
Human activity is the biggest contributor to carbon dioxide (CO2) gas into the air. Coastal ecosystems that have the ability to absorb and store carbon over a relatively long period of time are seagrass beds. Seagrass is able to absorb carbon with an average of 0.21 tons / ha. Research on Carbon Deposits in Seagrass in Tanjung Benoa Waters, Bali was conducted in February 2019. Determination of the sampling point was done by purposive sampling method. This research uses the dry ashing method which is carried out by crushing the sample components at 500?C in an electric furnace. Seagrass species obtained in Tanjung Benoa waters are Cymodocea Serrulata, Cymodocea Rotundata, Thalassia hemprichii, Syringodium isoetifolium, Halodule pinifolia, Halophila ovalis and Halodule uninevis . The results showed the seagrass density of Tanjung Benoa waters, Bali was included in the sparse to dense category with density values ??ranging from 195-1252 stands / m 2 . The content of seagrass carbon at the bottom of the substrate (roots and rhizoma) is 86.421 grams of dry weight (gbk / m 2 ), while the top of the substrate (leaves) is 33.774 grams of dry weight (gbk / m 2 ). The carbon content at the bottom of the substrate is higher than the top of the substrate because at the bottom of the substrate is not too affected by environmental physical factors. where the highest carbon content is Thalassia hemprichii seagrass with a value of 625.36 gC / m², while the lowest carbon content is Halophila ovalis with a value of 89.91 gC / m².